Case Report: Two cases of Hb Malay (HBB: c.59A>G) found in Northern Thailand - Theingi, Moe; Ruengdit, Chedtapak; Punyamung, Manoo; Pornprasert, Sakorn (Journal of Associated Medical Sciences, 2025)
Background: Hemoglobin (Hb) Malay is a common β-hemoglobinopathy in Malaysia resulting from an AAC to AGC mutation at codon 19, which produces an abnormal β-globin chain and manifests as a β+-thalassemia phenotype characterized by mild anemia and increased HbA2 levels. Although Hb Malay is commonly prevalent in Southern Thailand, there have been few reported cases in Northern Thailand. Objectives: This study aims to report two cases of Hb Malay detected in Chiang Mai, Northern Thailand, highlighting the diagnostic complexities. Materials and methods: Two female patients, aged 50 and 67, presenting with anemia were investigated. Initial hematological profiles, Hb analysis by HPLC (Case 1) and CE (Case 2), and iron studies were performed. Due to hypochromicmicrocytic anemia and elevated HbA2 levels in both cases, genomic DNA was extracted. Multiplex real-time PCR with HRM analysis was performed to detect common α0-thalassemia deletions. Further genetic analysis was conducted using next-generation sequencing (NGS) targeting HBA1, HBA2, and HBB genes. Results: Both cases were identified to carry the Hb Malay variant. Case 1, a 50- year-old female with mild anemia, was diagnosed with double heterozygosity for Hb Malay (βMalay/βA) and α+-thalassemia (-α3.7/αα). Case 2, a 67-year-old female with severe anemia and iron deficiency, was diagnosed with heterozygosity for Hb Malay (βMalay/βA). Conclusion: The diagnosis of Hb Malay can be complicated especially when it coexists with other thalassemia traits or iron deficiency. Therefore, better understanding of the hematological and clinical characteristics, as well as the laboratory detection of this hemoglobin variant, would be beneficial for genetic counseling, particularly in areas with a high prevalence of thalassemia, hemoglobinopathy, and iron deficiency such as Northern Thailand.